Renal sympathetic nerve activity regulates cardiovascular energy expenditure in rats fed high salt - Morisawa, Norihiko; Kitada, Kento; Fujisawa, Yoshihide; Nakano, Daisuke; Yamazaki, Daisuke; Kobuchi, Shuhei; Li, Lei; Zhang, Yifan; Morikawa, Takashi; Konishi, Yoshio; Yokoo, Takashi; Luft, Friedrich C.; et al. (Hypertension Research, 2020)
We recently reported that a 4% high-salt diet + saline for drinking (HS + saline) leads to a catabolic state, reduced heart rate, and suppression of cardiovascular energy expenditure in mice. We suggested that HS + saline reduces heart rate via the suppression of the sympathetic nervous system to compensate for the high salt intake-induced catabolic state. To test this hypothesis, we directly measured renal sympathetic nerve activity (RSNA) in conscious Sprague-Dawley (SD) rats using a radiotelemetry system. We confirmed that HS + saline induced a catabolic state. HS + saline decreased heart rate, while also reducing RSNA in SD rats. In contrast, Dahl salt-sensitive (DSS) rats exhibited no change in heart rate and increased RSNA during high salt intake. Renal denervation significantly decreased heart rate and attenuated the catabolic state independent of blood pressure in DSS rats fed HS + saline, suggesting that salt-sensitive animals were unable to decrease cardiovascular energy consumption due to abnormal renal sympathetic nerve activation during high salt intake. These findings support the hypothesis that RSNA mediates heart rate during high salt intake in SD rats. However, the insensitivity of heart rate and enhanced RSNA observed in DSS rats may be additional critical diagnostic factors for salt-sensitive hypertension. Renal denervation may benefit salt-sensitive hypertension by reducing its effects on catabolism and cardiovascular energy expenditure.
CRIS-Team Scopus Importer:2020-01-31
Keywords: Heart rate; Renal sympathetic nervous system; Salt; Salt-sensitive hypertension